Perceptual training of Arabic consonants in English-speaking learners of the Quran - Smith, Amanda A; Medina, Angela M; Rangarathnam, Balaji (Journal of Monolingual and Bilingual Speech, 2022)
In the Muslim community, accurate perception of classical Arabic phones is considered of importance in order to understand and recite the Quran, which is read, studied and recited in its original Arabic language. In this study, high variability phonetic training (HVPT) was used to train accurate perception of Arabic consonants that do not exist in American English. HVPT develops new phonemic categories by exposing learners to a variety of productions of new phonemes. Results indicated significant improvement in perception of Arabic consonants (pre-test mean = 58.5%, post-test mean = 64.8%, difference = 6.3%, w = 11, z = –1.36). Improvements were specifically seen for the contrasts /d-d/, /k-q/ and /h-h/. No significant relationship between HVPT outcomes and language learning variables was found. Overall results of the study indicate the effectiveness of training perception of Arabic phonemic contrasts in English-speaking learners of the Quran.